(3Pjd eQBI GdReGf aj JGQjN GdCYjGfs - (3ehSi Hf eMeO Hf CHj GdMSjf CMeO Gdjhfjfj GdHYdHcj, bWH GdOjf, CHh GdaJM , (B726 (3g` s; (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s
(3ChdgG (B:s
(3ef SfI (B671 s
(3BNQgG (B:s
(3Edi SfI (B689 s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B141 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdJGQjNs